The Growing Use of GMES across Europe's Regions - GEOmedia, Redazione (GEOmedia, 2013)
Una guida per i decisori politici sulle potenzialità e ibenefici derivanti dall'uso delle tecnologie di monitoraggiodella Terra nelle regioni Europee Abstract The Growing Use of GMES across Europe's Regions” LaunchEvent at the European Parliament.NEREUS – Network of European Regions Using Space Technologiesand ESA – European Space Agency, are pleased to announce the launch of a joint publication with the title "TheGrowing Use of GMES across Europe's Regions”, a collection of 67 illustrative articles on regional GMES applications. Addressed to a non-specialist audience, the collection illustrates the strategic value of the Programme for regional administrations and authorities in the context of territorial management and forward planning. The variety of existing andpotential regional uses across Europe shows how GMES not only contributes to better informed decision making but also how the data can be exploited to support sustainable environmental protection with a long term perspective. Quoting end user experiences, the publication gives a first-hand impression on the impact of GMES on regional development and policy implementation.